Twitter Verilerinden Kullanicilarin Siyasi E?ilimlerinin Veri Madencili?i Teknikleri ile Kestirimi - Safali, Yaşar; Avaro?lu, Erdinç; Ergen, Burhan (Institute of Electrical and Electronics Engineers Inc., 2019)
Social networks are an increasingly popular medias today. On these medias, users are able to interact with each other or share their views on an up-to-date topic, enabling them to have information about their own characters and worldviews. In this study, using the twitter data, the political tendency or parties supported by the users were predicted using data mining techniques. © 2018 IEEE.
2018 International Conference on Artificial Intelligence and Data Processing, IDAP 2018 -- 28 September 2018 through 30 September 2018 -- Malatya -- 144523
Keywords: data mining; Kappa test; machine learning; political opinion classification